Case report: a rare case of diffusely metastatic BRAF V600E-mutated colorectal cancer with concomitant infiltration of the skin and parotid gland - Boukouris, Aristeidis E.; Kokkinakis, Ioannis; Drakos, Elias; Sfakianaki, Maria; Tzardi, Maria; Mavroudis, Dimitrios; Souglakos, John (Frontiers in Oncology, 2025)
Metastastic disease affects up to 50% of colorectal cancer (CRC) patients and is associated with particularly poor outcomes in the presence of the BRAF V600E mutation. Herein, we report a patient with initial diagnosis of stage IIIc CRC, who presented during follow-up (adjuvant phase) with dysphagia, left-sided lagophthalmos and multiple skin nodules. The ensuing work-up revealed disseminated metastatic disease from the primary CRC, which was BRAF V600E-mutated (retrospective tissue analysis), affecting, besides the lungs, multiple uncommon sites, such as the skin and parotid gland. The patient’s rapid disease progression did not allow for any therapeutic interventions. This is only the second report of concomitant metastatic infiltration of the skin and parotid gland by CRC, and the first with a documented molecular background of BRAF V600E mutation. BRAF V600E-mutated CRC can follow an aggressive and often unpredictable clinical course in the metastatic setting that physicians should be aware of, and the molecular profile of the tumor at diagnosis could be useful for comprehensive and timely management.